STUDY OF THE STRUCTURE OF WOOD-RELATED BIOPOLYMERS BY SORPTION METHODS - Jelena Chirkova; Bruno Andersons; Ingeborga Andersone (BioResources, 2009)
The potentialities of different vapour sorption methods are analized for the investigation of the microstructure of wood sorbents (wood, cellulose and lignin) as a particular case of biopolymers. There are two important distinctions in the sorption behaviour of biopolymers from traditional rigid sorbents, namely, the dependence of the characteristics of the porous structure on the thermodynamic properties of the sorbate, and the manifestation of the sorption hysteresis over the whole region of the sorption–desorption isotherm. The reason for these distinctions is the low rigidity (low values of modulus of elasticity) of biopolymers, hence, their considerable deformability under the action of sorption forces, resulting in the cleavage of interstructural bonds. This process, manifesting itself phenomenologically as swelling, depends on the activity of the sorbate and results in the appearance of porosity and a new surface. The criterion for the activity of the sorbate is close values of the solubility parameters of the polymer and the sorbate. Inert substances are adsorbed on the surface of large morphological formations and characterise the intact structure of the sorbent, while active sorbates cause the swelling of these formations and penetrate them, which enables a study of the microstructure of sorbents. In the desorption process, the cleaved bonds are restored, blocking a part of the sorbate in the polymer’s structure, which results in the appearance of sorption hysteresis, not connected directly with the porous structure of the sorbent.